Legal Problems of Computer Abuse - Susan Hubbell Nycum (Washington University Law Quarterly, 1977)
Computer abuse consists of incidents caused by intentional acts from which a perpetrator realized or could have realized a gain and/or a victim suffered or could have suffered a loss. In this Article, Susan Hubbell Nycum discusses a wide variety of criminal acts relating to computers and notes that, because of the unique nature of the computer itself, these acts do not fit within traditional criminal classifications. Reform at both the state and federal levels is necessary if the law is to provide adequate protection for computer hardware and software users. The accelerating, almost uncontrolled increase in computer use affects the court system as well. The material presented herein is based on a multi-year study supported in part by the National Science Foundation. The study now includes an analysis of over 500 reported incidents of computer abuse.
Keywords: Criminal law; Criminal statistics